Digital Watermarking Implementation Of Digital Watermarking On Images Using The Least Significant Bit Method - Intan Setiawati; M. Thoni Hermanto; EIH Ujianto (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2023)
The ease of accessing the internet in this modern era has led to illegal crimes, especially data copying, data distribution and abuse of intellectual property rights. From these problems emerged a method of securing data and information, namely watermark. Watermark is used for data security techniques, both for copyright protection and digital signatures in the visible and invisible realms. One of the data security techniques used here is to use the least significant bit (LSB) method. This method is used for data security or images that contain watermarks, for example on currency there is usually a logo to distinguish real and fake currencies. This study uses nine host images taken from the https://www.kaggle.com/datasets/felicepollano/watermarked-not-watermarked-images dataset with different sizes, namely 513 x 513 pixels, 488 x 350 pixels, 467 x 350 pixels, 500 x 333 pixels, 512 x 301 pixels, 490 x 350 pixels, 500 x 332 pixels, 400 x 266 pixels, and 500 x 308 pixels. As for the label image, it uses the uty logo which has a size of 50 x 50 pixels, 80 x 80 pixels, and 124 x 124 pixels. From the results of the watermark test that has been carried out using the LSB method, the average PNSR value is 65 dB, so it can be concluded that the watermark research using the LSB method gets pretty good image results and can be used for data security. Keywords: Watermark, Least Significant Bit, Peak Signal to Noise Ratio (PNSR)